The 4th Schizophrenia International Research Society Conference, 5-9 April 2014, Florence, Italy: a summary of topics and trends - Abayomi, Olukayode; Amato, Davide; Bailey, Candace; Bitanihirwe, Byron; Bowen, Lynneice; Burshtein, Shimon; Cullen, Alexis; Fuste, Montserrat; Herrmann, Ana P.; Khodaie, Babak; Kilian, Sanja; Lang, Qortni A.; et al. (Schizophrenia Research, 2014)
The 4th Schizophrenia International Research Society Conference was held in Florence, Italy, April 5-9, 2014 and this year had as its emphasis, "Fostering Collaboration in Schizophrenia Research". Student travel awardees served as rapporteurs for each oral session, summarized the important contributions of each session and then each report was integrated into a final summary of data discussed at the entire conference by topic. It is hoped that by combining data from different presentations, patterns of interest will emerge and thus lead to new progress for the future. In addition, the following report provides an overview of the conference for those who were present, but could not participate in all sessions, and those who did not have the opportunity to attend, but who would be interested in an update on current investigations ongoing in the field of schizophrenia research.
EVALuna2:23659